Living, dead and fossil benthic foraminifera on a river dominated shelf (northern Gulf of Cadiz) and their use for paleoenvironmental reconstruction - Mendes, Isabel (2017)
Same-area comparison between patterns of Recent (living) and Holocene benthic foraminiferal assemblage composition is essential to validate their utility as proxies for paleoenvironmental reconstructions. Such reconstructions have scarcely been attempted in shelf environments. In this study, we compared living (stained), dead and Holocene benthic foraminiferal assemblages from the Gulf of Cadiz continental shelf off the Guadiana River. On average, 99% of the living benthic foraminiferal species were preserved in the dead assemblage and 95% in the fossil record. Several common species were assessed as indicators for certain environmental factors, including river discharge, supply of terrestrial organic matter, heavy metal concentrations, oxygen levels, substrate properties, hydrodynamic energy levels, sea-level rise and human impact. The paleoenvironmental reconstruction depicted five stages of Holocene environmental evolution of the Guadiana shelf over the last 11500 Cal yr BP. The characteristics of the stages, and the transitions between them, were in particular driven by changes in sea-level, influx of terrestrial organic matter and limits of productivity.